Discurso de inauguración del año académico 1986 - Valenzuela, Fernando (Revista Chilena de Humanidades, 2016)
Prof. Valenzuela, Dean of the F ::tculty of Philosophy, Humanities and Education, reflects upon the general situation of Chilean Universities today, in particular, that of the University of Chile, in the light of such concepts as autonomy, authority and legality. He makes a call towards the obtention of a genuine university fellowship in keeping with those values and objectives, humanistic as well as historicai, which have traditionally marked the academic life.